OPTIMAL SYNTHESIS OF STUB MICROWAVE FILTERS - Karpukov, L. M.; Voskoboynyk, V. O.; Savchenko, Iu. V. (Radio Electronics, Computer Science, Control, 2024)
Context. Microwave stub filters are widely used in radio engineering and telecommunication systems, as well as in technical information protection systems due to simplicity of design, possibility of realization in microstrip design and manufacturability in mass production. For synthesis of stub filters nowadays traditional methods based on transformation of low-frequency prototype filters on LC-elements into filtering structures on elements with distributed parameters are used. The transformations used are approximate and provide satisfactory results for narrowband stub filters. In this connection there is a necessity in development of direct synthesis methods for stub filters, excluding various approximations and providing obtaining of amplitude-frequency characteristics with optimal shape for any bandwidths. Objective. The purpose of the study is to develop a method for direct synthesis of stub band-pass filters and low-pass filters with Chebyshev amplitude-frequency response in the passband. Method. The procedure of direct synthesis includes the formulation of relations for filter functions of plume structures, selection of approximating functions of Chebyshev type for filter functions and formation of a system of nonlinear equations for calculation of parameters of filter elements. Results. A method for the direct synthesis of stub bandpass and lowpass filters with Chebyshev response is developed. Conclusions. Scientific novelty of the work consists in the development of a new method of direct synthesis of l stub filters. The method, in contrast to approximate traditional methods of synthesis of microwave filters, is exact, and the obtained solutions of synthesis problems are optimal. The experiments confirmed the performance of the proposed method and the optimality of the obtained solutions. Prospects for further research suggest adapting the method to the synthesis of filter structures with more complex resonators compared to stubs.